Theoretical Framework in Student Debt Research: Linking Economic, Finance and Education Theories to Student Debt Literature - Mbah, Ruth Endam (Advances in Social Sciences Research Journal, 2022)
There has been a growing interest in student debt research in recent years among researchers and graduate students. Student loan has become a popular means of financing the increasing cost of higher education among millennia, thus spurring the rising interest of researchers in this area. However, the availability of established theories related to the student debt topic is limited. The purpose of this study is to add to the limited literature of theories in student debt scholarship. This study links two economic theories, four finance theories, and two education theories to student debt literature. The economic theories (human capital theory and life cycle Model) emphasize the role of student loans in fostering investment in human capital and its impact on future consumption. This study also examines four debt repayment models (the debt snowball model, the balance-matching model, the debt avalanche model, and the debt consolidation model) suggested by various financial advisors on debt repayments, which postulate four distinct strategies on how debtors can settle their loans. The education theories (Tinto student departure model and John Bean’s explanatory theory of student retention model) highlight the importance of student retention at colleges to ensure college completion, which in turn increases the chances of getting a job; thus, guaranteeing loan repayment. These theories will serve as a theoretical framework guide to researchers, especially graduate students who are working on their thesis or dissertation on the student loan debt topic.